The prevalence and pattern of pediatric dermatoses in a tertiary care center at Garhwal, Uttarakhand, India - Singh, Ratan; Tiwari, Varun Kumar (International Journal of Contemporary Pediatrics, 2018)
Background: Analysis of skin diseases in the pediatric population and its trends reflects the health and nutritional status of a community. This study aimed to evaluate the prevalence and pattern of skin diseases in children registered at the Dermatology OPD department of Hemawati Nandan Bahuguna Teaching Base Hospital, Srikot over a period of 1 year. Methods: A prospective cross-sectional descriptive analysis was conducted at the Dermatology OPD department of HNB teaching hospital to determine the pattern of dermatoses in children aged 0 days to 17 years, between 1 April 2017 and 31 March 2018. Cases with incomplete data, non-compliant to treatment and patients whose primary lesions are altered by the application of topical medication, not related to the existing disease were excluded from the study. The results were entered and tabulated in MS-excel sheet and descriptive analysis was done. Results: Out of 23,359 outpatients 6,274 (26.85%) were of a pediatric age with a male to female ratio of 1.2:1. The majority of the children belonged to young teens and teenagers (2377;37. 88%). Majority of pediatric dermatoses belonged to Infectious group (1373;21.88%) followed by Disorders of skin appendages (1087;17.33%) and Infestations (722;11.5%). The three most common diagnoses were Scabies (694;11.06%) followed by Fungal infections (568;10.43%) and Acne vulgaris (398;6. 34%). Conclusions: This study showed the current pattern of pediatric dermatoses in Garhwal region of Uttrakhand with a high frequency of infection and infestations with young teen and teenagers as the identified focus group for the need of intervention.